2023
DOI: 10.7717/peerj.14658
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and metabolome response of eggplant against Ralstonia solanacearum infection

Abstract: Bacterial wilt is a soil-borne disease that represents ubiquitous threat to Solanaceae crops. The whole-root transcriptomes and metabolomes of bacterial wilt-resistant eggplant were studied to understand the response of eggplant to bacterial wilt. A total of 2,896 differentially expressed genes and 63 differences in metabolites were identified after inoculation with Ralstonia solanacearum. Further analysis showed that the biosynthesis pathways for phytohormones, phenylpropanoids, and flavonoids were altered in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The bacterial wilt resistance inbreed line NY cross between KY (highly susceptibility to bacterial wilt) [30] in the spring of 2021. The F 2 plants were generated in the fall of 2021.…”
Section: Development Of Mapping Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterial wilt resistance inbreed line NY cross between KY (highly susceptibility to bacterial wilt) [30] in the spring of 2021. The F 2 plants were generated in the fall of 2021.…”
Section: Development Of Mapping Populationmentioning
confidence: 99%
“…The RNA-seq data utilized in this study was obtained from our previous experiment focusing on the transcriptome and metabolome response of eggplant to R. solanacearum infection [30]. During the RNA-seq data, we referenced V3 reference genome [34].…”
Section: Combined Analysis Of Bsa-seq and Rna-seq For Screening Candi...mentioning
confidence: 99%
“…Research on the molecular and genetic framework of resistance to R. solanacearum has largely utilized Arabidopsis thaliana and Medicago truncatula model plants (Chen et al., 2019; Kover & Schaal, 2002; Roux et al., 2010; Vailleau et al., 2007), tomato (Prior et al., 1999; Yuliar et al., 2015), eggplant (Lebeau et al., 2013; Liu et al., 2016; Xiao et al., 2023), tobacco (Pan et al., 2021; Qian et al., 2013) and potato (Puigvert et al., 2017; Zuluaga et al., 2015). Various domesticated potato species, including S. phureja and closely associated wild species like S. chacoense , have been found to possess genetic resistance to bacterial wilt (Carputo et al., 2009; Habe et al., 2019; Liu et al., 2016; Puigvert et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to tobacco, different studies using different materials and methods have identified the involvement of the same pathway in BW resistance, namely the phenylpropane pathway [27][28][29], but also different pathways, including glutathione metabolism [28] and hormone-related pathways [29]. Phytohormones play a critical role in eggplant (Solanum melongena) resistance to BW as indicated by transcriptome and metabolome analyses [30]. Dual RNA-seq has revealed that inhibition of ethylene synthesis, promotion of photosynthesis, up-regulation of polysaccharide metabolism, and strengthening of cell wall defense can prevent the invasion of R. solanacearum in pepper [31].…”
Section: Introductionmentioning
confidence: 99%